Synthesis, characterisation, and crystallographic studies of sulfathiazole salts and related species / Siti Aina Mardia Akhmad Aznan - Siti Aina Mardia , Akhmad Aznan (2018)
Co-crystallisation of equimolar quantities of sulfathiazole (STL) with each of 1,4-diazabicyclo[2.2.2]octane (DABCO) and piperazine (PIP) resulted in facile formation of salts [DABCOH][STL_H] (1) and [PIPH][STL_H] (2), respectively. Crystallographic studies show the formation of aniline-N–H...O(sulfonyl) hydrogen bonds between anions to form supramolecular undulating and zigzag layers, respectively, with the cations being connected to these by charge-assisted N–H...N(thioazole) interactions. The salts formations were confirmed by 1H NMR, IR, Raman spectroscopies, CHN elemental analysis, Single Crystal X-ray Diffraction (SCXRD), Powder X-ray Diffraction (PXRD) and Differential Scanning Calorimetry (DSC) as well as melting point. Solid state grinding competition experiments were monitored by PXRD. In a sequence of experiments where STL was co-ground with a molar equivalent of PIP and n equivalents of DABCO (with n increasing from 0.1 to 1.0 in 0.1 increments), formation of salt 1 was observed. In related experiments where salt 2 was ground with an equimolar amount of DABCO, substitution of PIPH+ by DABCOH+ was evident, i.e., postsynthetic metathesis had occurred to about 70% for dry grinding. Quantitative yields were obtained in the case of liquid-assisted grinding (LAG) with a few drops of ethanol after 1.4 equivalents of DABCO were added. These observations are primarily correlated with differences in aniline-N–H...O(sulfonyl) hydrogen bonding that sustain the layers.